THE LEARNING RESULT DIFFERENCE OF STUDENT TEACH BY USING ENHANCEMENT LEARNING MODEL OF STUDENT’S THINKING ABILITY WITH CONVENSIONAL MODEL FOR FORCE AND NEWTON LAWS MATERIAL - Derlina .; Bintang Nainggolan (Universitas Negeri Medan, 2013)
This research was done to observe the difference of learning achievement between student who have been teach by Enhancement Learning Model of Student’s Thinking Ability and Conventional Model. This research was done at SMP Negeri 2 Gebang. Type of this research is quasi experiment. Research population is every student of grade VIII semester 2 SMP Negeri 2 Gebang. Research sample was taken by random sampling around 2 classes as 34 students for experiment class and 34 students for control class. Learning achievement of test objective 20 of multiple choice was done as an instrument. The experiment result of pretest average is 37.94 for experiment class and 36.82 for control class. Treatment was done to each class, post test average score is 73.38 for experiment class and for student who have been teach by conventional learning is 67.05. Hypothetical testing is tcalculate > ttabe i.e 3.459 > 1.66 with significance standard α = 0.05 and dk = 66. It means that Ha was accepted, so it may conclude that there is a difference of learning achievement between Enhancement Learning Model of Student’s Thinking Ability with Conventional Learning Model for Force and Newton Laws on Grade VIII SMP Negeri 2 Gebang Annual Year 2011/2012.